Art & humanities: annotated bibliography of UiTM libraries - Perpustakaan Tun Abdul Razak, Jabatan Sumber Rujukan Universiti (2022)
An Annotated bibliography covers library collections for the subject of Art & Humanities that are published once a year. The reading list is available in various formats obtained through the procurement process located at Perpustakaan Tun Abdul Razak in Shah Alam Campus and all other campuses in UiTM.